New strategies for the development of innovative fermented meat products: a review regarding the incorporation of probiotics and dietary fibers - Bis-Souza, C. V. [UNESP]; Barba, F. J.; Lorenzo, J. M.; Penna, A. L.B. [UNESP]; Barretto, A. C.S. [UNESP] (Taylor & Francis, 2019)
Over the last decades, consumer´s preference for and their attention to food products presented as healthy and with favorable nutritional information has been significantly increased. In this line, both the addition of dietary fiber and the incorporation of probiotic strains in the elaboration of fermented meat products has been established as a useful tool for the development of healthy products. Thus, the aim of this review is to present an overview of the studies involving fermented meat products with added dietary fiber and probiotic microorganisms, and also, to discuss about some of the challenges regarding the reformulation of this innovative product category.
Keywords: Fermented meat products; functional meat products; healthy; new food products; prebiotic fibers